Long-term forensic mental health services: an exploratory comparison of 18 European countries - Sampson, Stephanie; Edworthy, Rachel; Völlm, Birgit; Bulten, Erik (Taylor & Francis, 2016)
The objective of this study was to explore current provisions within forensic mental health inpatient services for people who require longer-term care within Europe. We used a structured questionnaire and follow-up semi-structured interviews with experts in forensic psychiatry in 18 European countries. All experts interviewed acknowledged the issue of ‘long-stay’ in forensic psychiatry with patient characteristics including chronic mental disorder, treatment-resistance and violent behavior. Formal and informal definitions of ‘long-stay’ varied widely between countries. Eight experts stated that long-stay services are currently available in their country. Of the countries without long-stay services, five experts expressed a need develop them. Improved quality of life and promotion of wellbeing were emphasized as the fundamental treatment philosophy. Even without an agreed definition of ‘long-stay’, it is clear that a proportion of mentally disordered offenders (MDOs) are ‘stuck’ in ‘the system’. Experts shared common concerns in terms of political pressures to contain dangerous MDOs for ensuring public safety as well as ethical debates regarding long-term forensic mental health care. Further research is required to promote dialogue between and within countries to address the balance of patient' rights and public safety, and to produce longitudinal and economic analyses of existing long-stay forensic service provisions.